Intense electroluminescence from ZnO nanowires. Issue 20 (28th May 2015) - Yang, Xun; Shan, Chong-Xin; Jiang, Ming-Ming; Qin, Jie-Ming; Hu, Guang-Chong; Wang, Shuang-Peng; Ma, Hong-An; Jia, Xiao-Peng; Shen, De-Zhen
<x xml:space="preserve">Abstract</x> Intense electroluminescence has been obtained from ZnO nanowires with holes injected from p-ZnO:Sb prepared via a high pressure high temperature method.